Inseparable modes or classical entanglement? - Leuchs, Gerd; Korolkova, Natalia (Proceedings Rochester Conference on Coherence and Quantum Optics, CQO 2019, 2019)
Mode functions may have the mathematical property of being inseparable. There has been a dispute on the relation of this property to the concept of quantum entanglement. We point out the similarities and the differences.
CRIS-Team Scopus Importer:2023-04-20